PEMBELAJARAN FISIKA BERBASIS PROBLEM BASED LEARNING BERPENDEKATAN SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS UNTUK MEMFASILITASI PENGEMBANGAN KETERAMPILAN KOMUNIKASI (UPEJ Unnes Physics Education Journal, 2022)
The Covid-19 pandemic has changed the learning process that was originally done conventionally into a distance education process, this condition causes various difficulties in participating in the learning process. The distance learning process is hampered by the difficulties of teachers in compiling media, to improve communication skills. The purpose of this research is to analyze the development of 21st-century learning skills of students with STEM-based learning using the PBL model. The research design used was a Quasi-Experimental Design using an analysis of the average communication skills from observations. The research sample of students of XI MIPA 2 SMA Negeri 3 Tegal amounted to 34 people. Skills Students' written communication skills are more prominent than oral communication with the highest average indicator, namely articulating ideas or ideas.